Protocol to boost the robustness and accuracy of spatial transcriptomics algorithms using ensemble techniques - Jiazhang Cai; Shushan Wu; Huimin Cheng; Wenxuan Zhong; Guo-Cheng Yuan; Ping Ma (STAR Protocols)
Summary: Spatial transcriptomics enhances our understanding of cellular organization by mapping gene expression data to precise tissue locations. Here, we present a protocol for using weighted ensemble method for spatial transcriptomics (WEST), which uses ensemble techniques to boost the robustness and accuracy of existing algorithms. We describe steps for preprocessing data, obtaining embeddings from individual algorithms, and ensemble integrating all embeddings as a similarity matrix. We then detail procedures for using the similarity matrix to identify spatial domains and obtain new embeddings.For complete details on the use and execution of this protocol, please refer to Cai et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.